In Search of the Greengrocer (Jak vykládat zelináře). Issue 2 (May 2018) - Day, Barbara
The author reflects on her experience teaching present-day students about life under totalitarianism. Forty years of Communism is a long time; attitudes and opinions matured and shifted—even (if we examine Havel's essay) those of his greengrocer. And what should be the focus of the teaching: the terror, the heroism, or the everyday business of living? How can one convey the different levels and subtleties of a world that history presents in black and white? The past could disappear in a hazy memory, but young people, once provoked, ask direct and practical questions that do connect the past to the present.